Cationic Thiolated Poly(aspartamide) Polymer as a Potential Excipient for Artificial Tear Formulations - Mária Budai-Szűcs; Gabriella Horvát; Barnabás Áron Szilágyi; Benjámin Gyarmati; András Szilágyi; Szilvia Berkó; Piroska Szabó-Révész; Giuseppina Sandri; Maria Cristina Bonferoni; Carla Caramella; Judit Soós; Andrea Facskó; et al. (Journal of Ophthalmology)
Dry eye disease is a relatively common ocular problem, which causes eye discomfort and visual disorders leading to a decrease in the quality of life. The aim of this study was to find a possible excipient for eye drop formulations, which is able to stabilize the tear film. A cationic thiolated polyaspartamide polymer, poly[(N-mercaptoethylaspartamide)-co-(N-(N′,N′-dimethylaminoethyl)aspartamide)] (ThioPASP-DME), was used as a potential vehicle. Besides satisfying the basic requirements, the chemical structure of ThioPASP-DME is similar to those of ocular mucins as it is a protein-like polymer bearing a considerable number of thiol groups. The solution of the polymer is therefore able to mimic the physiological properties of the mucins and it can interact with the mucus layer via disulphide bond formation. The resultant mucoadhesion provides a prolonged residence time and ensures protective effect for the corneal/conjunctival epithelium. ThioPASP-DME also has an antioxidant effect due to the presence of the thiol groups. The applicability of ThioPASP-DME as a potential excipient in eye drops was determined by means of ocular compatibility tests and through examinations of the interactions with the mucosal surface. The results indicate that ThioPASP-DME can serve as a potential eye drop excipient for the therapy of dry eye disease.